Medication Adherence and the Risk of Cardiovascular Mortality and Hospitalization Among Patients With Newly Prescribed Antihypertensive Medications. Issue 3 (March 2016) - Kim, Soyeun; Shin, Dong Wook; Yun, Jae Moon; Hwang, Yunji; Park, Sue K.; Ko, Young-Jin; Cho, BeLong
Abstract : The importance of adherence to antihypertensive treatments for the prevention of cardiovascular disease has not been well elucidated. This study evaluated the effect of antihypertensive medication adherence on specific cardiovascular disease mortality (ischemic heart disease [IHD], cerebral hemorrhage, and cerebral infarction). Our study used data from a 3% sample cohort that was randomly extracted from enrollees of Korean National Health Insurance. Study subjects were aged ≥20 years, were diagnosed with hypertension, and started newly prescribed antihypertensive medication in 2003 to 2004. Adherence to antihypertensive medication was estimated as the cumulative medication adherence. Subjects were divided into good (cumulative medication adherence, ≥80%), intermediate (cumulative medication adherence, 50%–80%), and poor (cumulative medication adherence, <50%) adherence groups. We used time-dependent Cox proportional hazards models to evaluate the association between medication adherence and health outcomes. Among 33 728 eligible subjects, 670 (1.99%) died of coronary heart disease or stroke during follow-up. Patients with poor medication adherence had worse mortality from IHD (hazard ratio, 1.64; 95% confidence interval, 1.16–2.31; P for trend=0.005), cerebral hemorrhage (hazard ratio, 2.19; 95% confidence interval, 1.28–3.77; P for trend=0.004), and cerebral infarction (hazard ratio, 1.92; 95% confidence interval, 1.25–2.96; P for trend=0.003) than those with good adherence. The estimated hazard ratios of hospitalization for cardiovascular disease were consistent with the mortality end point. Poor medication adherence was associated with higher mortality and a greater risk of hospitalization for specific cardiovascular diseases, emphasizing the importance of a monitoring system and strategies to improve medication adherence in clinical practice. Abstract : Supplemental Digital Content is available in the text.